Metoprolol--a new cardioselective beta-adrenoceptor blocking agent for treatment of tachyarrhythmias. - Wasir, H S (1977)
The antiarrhythmic effect of the cardioselective beta-adrenoceptor blocking agent metoprolol, given intravenously, was studied in 44 patients with various tachyarrhythmias, including patients with congestive heart failure and signs of digitalis intoxication. All patients with atrial tachycardia (12 cases) reverted to normal sinus rhythm. In 3 out of 18 patients with atrial fibrillation, sinus rhythm was restored, and in the others there was a significant reduction in ventricular rate. In 6 of 10 patients with ventricular ectopic beats, and 1 of 2 patients with ventricular tachycardia, the ectopic rhythm was abolished. The drug was well tolerated, without any significant changes in blood pressure, even by patients with signs of digitalis intoxication and varying degrees of pulmonary or peripheral circulatory congestion. Metoprolol is of clinical value for treatment of tachyarrhythmias, especially those of supraventricular origin.